Prostaglanin-E2 Potentiates the Suppressive Functions of Human Mononuclear Myeloid-Derived Suppressor Cells and Increases Their Capacity to Expand IL-10-Producing Regulatory T Cell Subsets - Tomić, Sergej; Joksimović, Bojan; Bekić, Marina; Vasiljević, Miloš; Milanović, Marijana; Čolić, Miodrag; Vučević, Dragana (Frontiers in Immunology, 2019)
Myeloid-derived suppressor cells (MDSC) emerged as major factors driving the tumor progression due to numerous immunosuppressive mechanisms they possess. Prostaglandin (PG)E2 is shown critical for the induction of MDSC and their suppressive functions in vivo, but it is poorly understood how it affects the capacity of MDSC to induce different subsets of regulatory T cells (Treg). By using a novel protocol for the generation of mononuclear (M)-MDSC, we showed that PGE2 potentiates the GM-CSF/IL-6-dependent induction of CD33+CD11b+HLA-DR-CD14+ M-MDSC in vitro. PGE2 diminished the capacity of GM-CSF/IL-6 M-MDSC to produce proinflammatory cytokines upon activation and augmented their capacity to produce IL-27, IL-33, and TGF-β. These results correlated with an increased potential of GM-CSF/IL-6/PGE2 M-MDSC to suppress T cell proliferation, expand alloreactive Th2 cells, and reduce the development of alloreactive Th17 and cytotoxic T cells. Interestingly, GM-CSF/IL-6/PGE2 M-MDSC displayed a lower capacity to induce TGF-β-producing FoxP3+ regulatory Treg compared to GM-CSF/IL-6 M-MDSC, as a consequence of reduced IDO-1 expression. In contrast, GM-CSF/IL-6/PGE2 M-MDSC potentiated IL-10 production by CD8+T, Th2, and particularly CD4+FoxP3- type 1 Treg, the latter of which depended on ILT3 and ILT4 expression. Cumulatively, PGE2 potentiated the suppressive phenotype and functions of GM-CSF/IL-6-induced M-MDSC and changed the mechanisms involved in Treg induction, which could be a good model for investigating new therapeutic strategies focused on MDSC-related effects in tumors and autoimmune diseases.